Pengaruh Modal, Kemasan, dan Lama Usaha terhadap Pendapatan Pedagang Kaki Lima di Jakarta Timur - Herwanto, Muhammad Ravi; Mukhtar, Saparuddin; Herlitah, Herlitah (Peradaban Journal of Economic and Business, 2025)
The informal sector plays a strategic role in Indonesia’s economy; however, several business actors, such as street vendors, still face various challenges that affect their income levels. This study aims to analyze the effect of capital, packaging, and business duration on the income of street vendors in the urban informal sector. A quantitative approach was employed using a survey method involving 134 street vendor respondents in East Jakarta. The data were analyzed using multiple linear regression with the assistance of SPSS. The results reveal that capital, packaging, and business duration have a positive and significant effect on income, although the Adjusted R Square value indicates that most of the variation in income is influenced by other factors outside the model. These findings highlight the importance of combining production factors to improve the financial performance of street vendors and reinforce the relevance of the Cobb–Douglas production theory in the context of the informal sector. The practical implications of this research can be utilized by local governments and MSME empowerment institutions in designing assistance programs and business training strategies aimed at enhancing productivity.and MSME development institutions in designing support and training programs aimed at improving productivity. Sektor informal memiliki peran strategis dalam perekonomian Indonesia, namun beberapa pelaku usaha seperti pedagang kaki lima, masih dihadapkan pada beberapa kendala yang memengaruhi tingkat pendapatan mereka. Penelitian ini bertujuan untuk menganalisis pengaruh modal, kemasan, dan lama usaha terhadap pendapatan pedagang kaki lima (PKL) di sektor informal perkotaan. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei terhadap 134 responden PKL di kawasan Jakarta Timur. Teknik analisis yang digunakan adalah regresi linear berganda dengan bantuan SPSS. Hasil penelitian menunjukkan bahwa  modal, kemasan, dan lama usaha berpengaruh positif dan signifikan terhadap pendapatan meskipun nilai Adjusted R Square menunjukkan bahwa sebagian besar variasi pendapatan dipengaruhi oleh faktor lain di luar model. Temuan ini menegaskan pentingnya kombinasi faktor produksi dalam meningkatkan kinerja keuangan PKL, serta mendukung penguatan teori produksi Cobb-Douglas dalam konteks sektor informal. Implikasi praktis dari penelitian ini dapat digunakan oleh pemerintah daerah dan lembaga pemberdayaan UMKM dalam menyusun strategi bantuan dan pelatihan usaha berbasis peningkatan produktivitas.